Artifact classification : a conceptual and methodological approach - Read, Dwight W., 1943- (Left Coast Press, 2007)
"Archaeologists have been developing artifact typologies to understand cultural categories for as long as the discipline has existed. Dwight Read examines these historically through a study of various attempts at pottery typologies. He then offers his own sophisticated methodology for classifying any sort of artifact. His typologies are designed to be both salient to the cultural groups that produced them and relevant to the archaeologist trying to establish cultural categories and timelines. The methodology also helps us to understand the relationship between material culture and ideational culture in ancient societies. This volume should be invaluable to upper level students and professional archaeologists attempting to categorize groups of artifacts."--BOOK JACKET.